Improving university students' entrepreneurial attitude through learning by doing method - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (The Journal of International Social Research, 2010)
Employing effective pedagogy methods has been considered as influential in developing students’ attitudes toward entrepreneurship. However, there is limited empirical research on the impact of entrepreneurship pedagogical methods on students’ attitudes toward entrepreneurship. The core purpose of this study was to determine the influence of “learning by doing”, as one of the most suggested entrepreneurship pedagogy methods, in enhancing different aspects of students’ entrepreneurial attitude. A total of 193 students from one university in Malaysia were selected as respondents. The findings indicate that university students who had undertaken entrepreneurship course through “learning by doing” pedagogy scored significantly higher in achievement behaviour, achievement cognition, self-esteem cognition, and innovation cognition compared to their counterparts. However, t-test analysis was conducted to identify differences on entrepreneurial attitude based on students’ entrepreneurial aspiration. Findings revealed that students with positive aspiration toward entrepreneurship scored higher mean and significantly different compared to the others for most of the entrepreneurship attitude aspects.